Panethniki diaskepsi yia ta pirinika kai tis vasis (Peace National Independence Steering Committee, 1986)
Black silhouette of a human holding a dove, over white background Poster advertising conference on nuclear weapons and military bases, held in Athens, 28-29 June, 1986 PO-1324